Kematangan Beragama sebagai Prediktor Konsistensi Perilaku Ibadah Siswa SMA NU Palangka Raya - Fazrah Ainun Nisa; Andini Indah Hasanah; Dai Bahtiar; Muhammad Anwar; Surawan Surawan (Lentera: Jurnal Ilmiah Kependidikan, 2026)
This study aims to analyze religious maturity as a predictor of the consistency of students’ worship behavior at SMA NU Palangka Raya. This research employed a quantitative approach with a correlational design. The sample consisted of 35 students selected using purposive sampling technique. Data were collected through a questionnaire using a Likert scale, and analyzed using simple linear regression with the assistance of SPSS. The results showed that the levels of religious maturity and consistency of worship behavior among students were categorized as high. The regression analysis indicated that religious maturity had a positive and significant effect on the consistency of worship behavior, with a significance value of 0.000 (< 0.05). The coefficient of determination (R Square) value of 0.861 indicates that 86.1% of the variance in the consistency of worship behavior can be explained by religious maturity, while the remaining is influenced by other factors. These findings suggest that religious maturity is a crucial factor in shaping students’ consistency in worship behavior. Therefore, strengthening religious maturity through religious education needs to be optimized in order to develop students’ religious character and sustainable worship habits.